1996
DOI: 10.5089/9781451962123.001
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Implications of Money Laundering

Abstract: This is a Working Paper and the authors) would welcome any comments on the present text Citations should refer to a Working Paper of the International Monetary Fund, mentioning the author(s). and the date of issuance. The views expressed are those of the authors) and do not necessarily represent those of the Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 14 publications
2
36
0
7
Order By: Relevance
“…The negative correlation between ML and GDP generated by our model is consistent with the empirical results of Quirk (1996), whose empirical tests conducted on the relationship between GDP growth and ML in 18 industrial countries found evidence that significant reductions in annual GDP growth rates were associated with increases in the laundering of criminal proceeds in the period 1983-1990. …”
Section: Money Laundering and Aggregate Gdpsupporting
confidence: 87%
See 1 more Smart Citation
“…The negative correlation between ML and GDP generated by our model is consistent with the empirical results of Quirk (1996), whose empirical tests conducted on the relationship between GDP growth and ML in 18 industrial countries found evidence that significant reductions in annual GDP growth rates were associated with increases in the laundering of criminal proceeds in the period 1983-1990. …”
Section: Money Laundering and Aggregate Gdpsupporting
confidence: 87%
“…Firms and households use the criminal sector to carry out criminal offences and ML to hide the revenues of these activities in the formal economy. In this respect, ML represents the link between the criminal economy, as a particular subset of illegal 7 economy, and the formal Quirk (1996)-IMF 1983-1990INDIRECT FATF-GAFI (2006 Cases study (2006) INDIRECT 6 Wen and Love (1998) describe the hours spent in transacting by a function in which this cost is proportional to the tax rate on consumption goods and to the velocity of money in terms of consumption; moreover, they insert this cost in the utility function as an element able to reduce the leisure for the households. We follow their approach in the choice of including the transaction cost in the utility function, but we model the hours spent in transacting proportionally to the consumption of legal economy good.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this may increase the risk inherent to a monetary instability and leads to a misallocation of resources and creates distortions in the prices of goods and financial assets. Quirk (1996) 9 and Camdessus (1998) have tried to study the effects of money laundering on the stability of the economy, and the financing of investment. They concluded that money laundering may result in adverse changes in the money demand and increases the volatility of international capital flows, exchange rates and interest rates.…”
Section: At the Macroeconomic Levelmentioning
confidence: 99%
“…2) замедление роста экономики [Quirk P. J., 1997]. Кроме того, ряд экономистов отмечает, что отмывание денег дестабилизирует общество, порождая: 1) ослабление социальной структуры: средства, полученные преступными организациями, а также в результате уклонения от уплаты налогов, являются основой воспроизводства и расширения мощи организованных преступных групп, роста доходов преступников и потери прибыли легальной экономики;…”
Section: потребностиunclassified